2015
DOI: 10.2147/ijwh.s70314
|View full text |Cite
|
Sign up to set email alerts
|

Complications and challenges associated with polycystic ovary syndrome: current perspectives

Abstract: Polycystic ovary syndrome (PCOS) represents the most common endocrine dysfunction in fertile women and it is considered a heterogeneous and multifaceted disorder, with multiple reproductive and metabolic phenotypes which differently affect the early- and long-term syndrome’s risks. Women with PCOS present an adverse reproductive profile, including a high risk of pregnancy-induced hypertension, preeclampsia, and gestational diabetes mellitus. Patients with PCOS present not only a higher prevalence of classic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
141
3
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(167 citation statements)
references
References 193 publications
2
141
3
14
Order By: Relevance
“…Moreover, because of the association of PCOS with insulin resistance, evidence suggests that women with PCOS are at an increased risk for developing type-2 diabetes, dyslipidemia, hypertension, and heart disease. 7 The cysts are not harmful but lead to hormone imbalances. 8 Risk factors include obesity, not enough physical exercise, and a family history of someone with the condition during this pubertal transition, several features may be in evolution and thus many findings may be transitory which stabilize later during adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because of the association of PCOS with insulin resistance, evidence suggests that women with PCOS are at an increased risk for developing type-2 diabetes, dyslipidemia, hypertension, and heart disease. 7 The cysts are not harmful but lead to hormone imbalances. 8 Risk factors include obesity, not enough physical exercise, and a family history of someone with the condition during this pubertal transition, several features may be in evolution and thus many findings may be transitory which stabilize later during adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…whilst the prevalence rate is 10% when using NIH criteria for diagnosis criteria [3] but the prevalence is still unknown in children [2] [4]. Three different criteria have been implemented for the diagnosis of PCOS: the NIH criteria (1990), the Rotterdam criteria (2003) and the Androgen and PCOS society (AE-PCOS) criteria (2006) [5] [6].…”
mentioning
confidence: 99%
“…Although its etiology has not been fully clarified, genetic and environmental factors have been implicated [15]. Currently, there are three main diagnostic classification systems that have been proposed for the diagnosis of [16], and in a recent study, Enck et al demonstrated that abdominal obesity is a significant risk factor for IBS [18].…”
Section: Discussionmentioning
confidence: 99%